2022
DOI: 10.1111/tpj.16005
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence ofHirschfeldia incana, a new Brassicaceae model to improve photosynthetic light‐use efficiency

Abstract: SUMMARY Photosynthesis is a key process in sustaining plant and human life. Improving the photosynthetic capacity of agricultural crops is an attractive means to increase their yields. While the core mechanisms of photosynthesis are highly conserved in C3 plants, these mechanisms are very flexible, allowing considerable diversity in photosynthetic properties. Among this diversity is the maintenance of high photosynthetic light‐use efficiency at high irradiance as identified in a small number of exceptional C3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 138 publications
2
28
1
Order By: Relevance
“…To resolve the phylogenetic relationships of the two H. incana accessions HIR1 and HIR3 from our study and another accession, NIJ, previously reported in Garassino et al (2022), we constructed phylogenetic trees. Our phylogenetic tree based on the LSC regions of 14 Brassiceae chloroplast genomes had high support values for all nodes (SH‐aLRT/bootstrap >70%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To resolve the phylogenetic relationships of the two H. incana accessions HIR1 and HIR3 from our study and another accession, NIJ, previously reported in Garassino et al (2022), we constructed phylogenetic trees. Our phylogenetic tree based on the LSC regions of 14 Brassiceae chloroplast genomes had high support values for all nodes (SH‐aLRT/bootstrap >70%).…”
Section: Resultsmentioning
confidence: 99%
“…Our phylogenetic tree based on the LSC regions of 14 Brassiceae chloroplast genomes was consistent with the topology reported in previous studies (Arias & Pires, 2012; Koch & Lemmel, 2019). In this tree, the two H. incana accessions were placed together with the NIJ accession (Garassino et al, 2022)⁠ on the same branch. However, our result suggests that HIR3 is genetically different from the HIR1 and NIJ accessions (Figure 6a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means while both the physiological and genetic potential for increased photosynthesis is present, in nature plants perform at an optimum determined by the constraints of the environmental conditions. environments, with low competition and low biotic disease pressure, they show close to maximal photosynthesis (Mooney et al, 1976;Ehleringer, 1983;Garassino et al, 2022;Taylor et al, 2022).…”
Section: What Novel Insights Do the Causal Genetic Variants Reveal?mentioning
confidence: 99%